A Heterodox Publishing Enterprise of the Thirty Years' War: Additions to the Catalogue of Hans Fabel's Publications. (14th August 2018) - Penman, Leigh T I
Abstract: This bibliographical note reports on the discovery of six further imprints issued by the publishing house of Hans Fabel. Between 1645 and 1650, Fabel operated a printing office in Amsterdam dedicated to the print and publication of heterodox religious works in the German language. This update documents and bibliographically describes tracts by Ludwig Friedrich Gifftheil, Lorenz Grammendorf, and an anonymous author, which were issued by Fabel between 1647 and 1649. These prints suggest further Fabel's own commitment to religious reform based on spiritualist doctrines as a motivating factor in the establishment of his printery. Furthermore, the note adds some further detail to Fabel's failed plan to publish the works of Jacob Boehme in German and Latin editions.